Involvement of microRNA/cystine/glutamate transporter in cold-stressed gastric mucosa injury - Yin, You-Cong; Li, Xiao-hui; Rao, Xuan; Li, Yuan-Jian; Du, Jie (Frontiers in Pharmacology, 2022)
Stress ulcers are complicated by severe trauma and other critical diseases, the mechanism of which remains unclear. An increasing number of studies have shown that microRNAs (miRNAs) are important regulators of stress responses such as hypoxia, abnormal temperature, and inflammation. The evidence indicates that miRNAs are also involved in regulating stress-induced ulcers. Recently, we demonstrated that gastric mucosal injury induced by aspirin is related to the reduction of glutamate levels by inhibition of cystine/glutamate transporter (xCT) activity. In the present study, the effect of a miRNA/xCT on gastric mucosal injury induced by cold stimulation was investigated. We found that cold stimulation induced gastric mucosa injury with a reduction in glutamate levels and xCT activity and upregulation of miR-143, miR-152, and miR-181 expression. Exogenous glutamate significantly alleviated gastric mucosa injury by cold stimulation. In vitro experiments demonstrated that treatment with miR-143, miR-152, or miR-181 directly induced cell damage. The effects of these mimics were alleviated by exogenous glutamate. The present study suggests that miR-143, miR-152, and miR-181 are involved in cold stimulation-induced acute gastric mucosal injury. Furthermore, the regulatory effect of miRNAs on gastric mucosa injury induced by cold stimulation is related to a decrease in glutamate release by reduction of cystine/glutamate transporter activity.